PENGARUH PENAMBAHAN PLASTIK LOW LINIER DENSITY POLYETHYLENE (LLDPE) PADA LAPISAN ASPAL BETON (AC-BC) DITINJAU DARI KARAKTERISTIK MARSHALL - Mokoginta, Ilham; Erwan, Komala; Sulandari, Eti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
This study was conducted to determine the effect of the addition of LLDPE to laston asphalt mixture AC-BC. From the test results pertamina 60/70 bitumen mixed with LLDPE, showed the value of penetration, ductility, and the flash point and fuel has decreased while the value of the softening point increases with levels of LLDPE, so that when the greater levels of LLDPE were mixed into the asphalt then there are some that do not meet the test of asphalt 2010 general specifications (Revision 3), especially penetration and ductility. Next, the plan done by using a mixture of pure asphalt and aggregate compositions to rock 1-2 (19%), Stone 1-1 (23%), sand (23%), and the gray stone (35%) and then make a test specimen of 15 fruit, with asphalt content range of 5.5% - 7.5%. Based on the results of the analysis proved that the plastic (LLDPE) affect the asphalt mixture laston AC-BC, but not significant as there some marshall parameters whose value increases but the difference in the value of each variation are not too large, there is also the value goes down but the impairment is still eligible specifications. Along with increasing levels of LLDPE were mixed into the asphalt, at a level of 0.4% LLDPE show the best value from the fifth variation, because all the testing properties qualify marshall Highways specification revision III in 2010, with a value of 1215.87 stability kg, the value of flow of 3.90 mm, MQ value of 314.01 kg / mm, the value VIM 4.95%, amounting to 17.03% of VMA value, and the value of VFB amounted to 81.62%.Â Keywords : Plastics Linear Low Density Polyethylene (LLDPE), Asphalt Concrete-